Wheat growth as influenced by application of agroforestry-tree prunings in Ethiopian highlands - Anthofer, J.; Hanson, Jean; Jutzi, S.C. (Springer, 1998)
The response of wheat (Triticum aestivum cv. ‘Enkoy’) to application of leaf prunings of nine agroforestry-tree species was investigated in a field trial and a six-week pot trial. The tree species were Grevillea robusta, Erythrina abyssinica, Gliricidia sepium, Albizia schimperiana, Acacia nilotica, Acacia polyacantha, Leucaena leucocephala, Leucaena pallida and Entada abyssinica. L. leucocephala, L. pallida, G. sepium and Entada abyssinica proved to be good pruning sources in the pot trial. G. robusta, A. polyacantha, A. nilotica and E. abyssinica had adverse effects on wheat seedlings with increased pruning loads probably due to immobilization processes or allelopathic effects. N and lignin content, C/N ratio, lignin/N ratio, phenolics/N ratio and (phenolics + lignin)/N ratio of the pruning material were all significantly correlated with shoot dry matter production of the wheat seedlings. With the exception of Entada abyssinica, which performed well under field conditions, a similar ranking as in the pot trial was established in the field experiment, but at harvest differences were not as pronounced as in the pot trial. Gliricidia treated wheat produced by far the highest grain yield with 248 g/m2.